L’approche bilingue et l’apprentissage de la lecture chez les sourds - Daigle, Daniel; Armand, Françoise (Canadian Journal of Applied Linguistics, 2004)
The bilingual and bicultural approach in the education of deaf students causes a growing interest in deaf communities, specialists, and deaf children’ parents (Cummins and Danesi, 1990; Mahshie, 1995). This approach is based, among other things, on the role of L1 (sign language) on the learning experience in L2 (majority language). According to the supporters of this approach, a deaf pupil who know enough a sign language before starting school would benefit from this experience in later majority language acquisition, notably in reading. In this paper, we will present the bilingual and bicultural approach by defining first what reading is, especially in terms of words recognition processes, and then by questioning the role played by the sign language in reading acquisition among deaf students. We will defend the idea that the early acquisition of a sign language is capital (Virole, 1993s; Padden and Ramsey, 1998; Strong and Printz, 2000) and that phonology awareness of the majority language is essential to reading success (Musselman, 2000; Perfetti and Sandak, 2000).